Miniaturized high-throughput conversion of fungal strain collections into chemically characterized extract libraries for antimicrobial discovery - Bory, Alexandre; Luscher, Alexandre; Lecoultre, Nicole; Köhler, Thilo; Schnee, Sylvain; Gindro, Katia; Wolfender, Jean-Luc (Frontiers in Chemistry, 2025)
Natural products remain vital to drug discovery, with fungi representing an underexplored source of bioactive compounds. Despite advances in LC-MS-based metabolomics that facilitate dereplication and chemical profiling of natural extracts, the rate of new discoveries has not significantly increased. This stagnation may be attributed to the laborious process of culturing and extracting large microbial collections. At the same time, rising antimicrobial resistance, particularly among ESKAPE pathogens, highlights the urgent need for new scaffolds. To address these challenges, we developed FLECS-96 (Fungal Library Extract Conversion and Screening in 96-well plate format), a high-throughput platform that efficiently transforms fungal strains into chemically characterized extract libraries. FLECS-96 combines miniaturized fungal liquid culture with streamlined sample preparation, systematic metabolomic profiling, and biological evaluation of the extracts. Here, we describe the development and validation of this workflow, and demonstrate its utility through the rapid identification of compounds active against S. aureus. FLECS-96 provides a scalable solution to accelerate antimicrobial lead discovery from fungal sources.